Increasing Students’ Speaking Ability in Procedure Text by Using Cooperative Learning - Siti Rohemah; Fabiola D. Kurnia; Eka Fadilah (Budapest International Research and Critics University, 2022)
It was the primary objective of this classroom action research project to improve students' oral communication skills in procedure text by utilizing cooperative learning. Statistical analysis was performed on the data in this study, using both quantitative and qualitative data. The fluency, performance, and completeness of the students' task are the primary focus of this study. The subjects of the study were students in the ninth grade of Junior High School YAS'A Sumenep, who participated in the study. The score of the students was used as the basis for this investigation. This research employed a two-cycle approach that included planning, implementing, observing, and reflecting. The findings of this study revealed that students were enthusiastic about cooperative learning when it was implemented as a method over a two-cycle period. It can be concluded that cooperative learning increased student speaking ability because 95 percent of the students who passed the Criteria Minimum Score (KKM) achieved success in their scores, and that cooperative learning increased student speaking ability because it increased student speaking ability.